Usefulness of a scoring system in the interpretation of histology in neonatal cholestasis. - Lee, W.S.; Looi, L.M. (2009)
A 7-feature, 15-point histological scoring system had good diagnostic accuracy in the interpretation of liver histology in neonatal cholestasis.